LONGITUDINAL STUDY OF COAGULATION CHANGES IN PEDIATRIC ITP PATIENTS - To’ymurodova Zarinabonu Elmurod qizi (INTEGRATION OF EDUCATION AND SCIENCE: GLOBAL CHALLENGES AND SOLUTIONS, 2026)
This study investigates longitudinal changes in coagulation parameters in children diagnosed with idiopathic thrombocytopenic purpura (ITP). Pediatric ITP is an autoimmune disorder characterized by isolated thrombocytopenia, leading to an increased risk of bleeding. While platelet counts remain the primary marker for disease monitoring, evaluating changes in coagulation parameters over time provides a more comprehensive understanding of hemostatic function and bleeding risk. This study follows pediatric ITP patients longitudinally, analyzing standard coagulation tests, platelet function, and advanced hemostatic markers to identify trends, predict complications, and inform individualized management strategies.